Psychocorrection of manifestations of socio-psychological disadaptation of combatants - Kochubynska, Tamara (Psychological Prospects Journal, 2021)
Purpose. The purpose of the study is theoretical construction and approbation of the author’s method of psychocorrection of manifestations of socio-psychological disadaptation of the participants of the Joint Forces operation (JFO). Methods. The following research methods were applied to achieve the aim of the study: theoretical: philosophical and psychological analysis of the study, generalization of theoretical and methodological approaches, modelling and construction; empirical: forming experiment using the psychodiagnostic complex of techniques; methods of mathematical data processing: comparative analysis using Student’s t-test. The implementation of the psycho-correctional program took place according to 5 stages: diagnostic, informational and educational, individual psychocorrection, group psychocorrection, and evaluation of effectiveness. Thirty-eight participants of JFO took part in the proposed psycho-correctional program. The experimental research was conducted with 40 combatants of JFO who did not participate in the psycho-correctional program to establish the reliability of the psycho-correctional program, namely to exclude the probability of age-related dynamic changes. Results. The proposed program represents the means of psycho-correctional effect: the educational block (lectures, training seminars, programs of social and psychological support) and the block of psycho-correctional work (individual and group psychocorrection) are singled out, that influenced the manifestations of social and psychological disadaptation of participants of JFO and contributed to the emergence of constructive personal changes. The main task of the psycho-correctional program is personal changes of JFO participants, harmonization of Self-concept in particular. Emotional constituent comprises increasing the level of manifestation of emotional comfort and reducing the level of manifestation of negative emotions (anxiety, aggression, depression). Сommunicative constituent includes increasing the communicative potential and constructive ways of interaction. Behavioural constituent embodies the development of constructive behavioural strategies, motivational and value constituent comprises harmonization of externality and internality, increasing motivation to overcome barriers, and constructive value orientations. According to the results of the comparative analysis using Student’s t-test for dependent samples, the qualitative differences in the indicators of socio-psychological disadaptation of JFO combatants before and after participation in the psychocorrection program were determined. The manifestations of indicators on the Physical Self and Familial Self scales have decreased. Manifestations of aggression, in particular feelings of resentment, physical and personality anxiety, disadaptation, self-rejection, emotional discomfort, internal control have reduced. Conclusions. The results of the forming research experiment confirm the effectiveness of the proposed program of psychocorrection.